Effect of Substituting Pure Sucrose by Sugarcane Juice as Carbon Source on the Fermentation of Dextran Production - Triantarti Triantarti; Hendro Santoso M (Fakultas Matematika dan Ilmu Pengetahuan Alam Universitas Jember, 2007)
Sucrose is a carbon source for dextran fermentation and it is also used as a substrate of dextransucrase enzyme for producing dextran. Sugar cane juice containing sucrose as a main sugar, hence it is potential to be used as a cheap medium for dextran fermentation. This research was conducted to study the dextran fermentation using sugar cane juice as a medium. Two main experiments were done in this research. The first experiment has been carried out to determine the optimum medium composition for dextran fermentation using pure sucrose as a carbon source by variations on type and concentrations of yeast extract and buffering minerals. The second experiment was conducted to determine the effect of substituting pure sucrose in the fermentation medium by sugar cane juice. Fermentation was conducted at static condition, room temperature and 16-20 h fermentation time. The results showed that the optimum conditions for dextran fermentation using pure sucrose were sucrose 20%, yeast extract 0.75% (technical grade yeast extract was able to be used) and K2HPO4 minerals for buffering medium. Dextran production was able to reach 51 mg/g medium. The optimum medium composition and fermentation conditions were used as a control medium. In the second experiment, pure sucrose in the control medium was substituted by sugar cane juice with variations of 0; 50, 75 and 100%. Technical grade yeast extract was still added at 0.75%. The result showed that the higher sugar cane juice concentration the lower dextran production in the fermentation. On the other hand, medium fermentation containing 100% sugar cane juice without yeast extract was able to produce 45 mg dextran/g medium, which was not significantly different to dextran production from control medium. This experiment showed that sugar cane juice was a potential material as a cheap carbon source for dextran fermentation